A Multi-Biochemical and In Silico Study on Anti-Enzymatic Actions of Pyroglutamic Acid against PDE-5, ACE, and Urease Using Various Analytical Techniques: Unexplored Pharmacological Properties and Cytotoxicity Evaluation - Šudomová, Miroslava; Hassan, Sherif T S; Khan, Haroon; Rasekhian, Mahsa; Nabavi, Seyed Mohammad (Biomolecules, 2019)
In the current study, pyroglutamic acid (pGlu), a natural amino acid derivative, has efficiently inhibited the catalytic activities of three important enzymes, namely: Human recombinant phosphodiesterase-5A1 (PDE5A1), human angiotensin-converting enzyme (ACE), and urease. These enzymes were reported to be associated with several important clinical conditions in humans. Radioactivity-based assay, spectrophotometric-based assay, and an Electrospray Ionization-Mass Spectrometry-based method were employed to ascertain the inhibitory actions of pGlu against PDE5A1, ACE, and urease, respectively. The results unveiled that pGlu potently suppressed the activity of PDE5A1 (half-maximal inhibitory concentration; IC50 = 5.23 µM) compared with that of standard drug sildenafil citrate (IC50 = 7.14 µM). Moreover, pGlu at a concentration of 20 µg/mL was found to efficiently inhibit human ACE with 98.2% inhibition compared with that of standard captopril (99.6%; 20 µg/mL). The urease-catalyzed reaction was also remarkably inactivated by pGlu and standard acetohydroxamic acid with IC50 values of 1.8 and 3.9 µM, respectively. Remarkably, the outcome of in vitro cytotoxicity assay did not reveal any significant cytotoxic properties of pGlu against human cervical carcinoma cells and normal human fetal lung fibroblast cells. In addition to in vitro assays, molecular docking analyses were performed to corroborate the outcomes of in vitro results with predicted structure-activity relationships. In conclusion, pGlu could be presented as a natural and multifunctional agent with promising applications in the treatment of some ailments connected with the above-mentioned anti-enzymatic properties.
Keywords: Cyclic Nucleotide Phosphodiesterases, Type 5; Protein Structure, Tertiary; Cell Line; anti-enzymatic properties; sildenafil citrát; Pyrrolidonecarboxylic Acid; Urease; pyroglutamic acid; simulace molekulového dockingu; ESI-mass spectrometry; Peptidyl-Dipeptidase A; Spectrophotometry; angiotensin-converting enzyme; rekombinantní proteiny; Captopril; phosphodiesterase 5; urease; kaptopril; Spectrometry, Mass, Electrospray Ionization; Molecular Docking Simulation; cytotoxicity; ureasa; cyklické nukleotidfosfodiesterasy, typ 5; angiotensin konvertující enzym; vazebná místa; kyselina pyrrolidonkarboxylová; vztahy mezi strukturou a aktivitou; Humans; Binding Sites; kyseliny hydroxamové; spektrofotometrie; inhibiční koncentrace 50; viabilita buněk; Cell Survival; Sildenafil Citrate; Inhibitory Concentration 50; buněčné linie; hmotnostní spektrometrie s elektrosprejovou ionizací; Structure-Activity Relationship; terciární struktura proteinů; lidé; Recombinant Proteins; Hydroxamic Acids